STRATEGI PEMBERDAYAAN MASYARAKAT DALAM PEMBENTUKAN KARAKTER ANAK MELALUI PENDIDIKAN - Setyowati, Dinan Anggun; Aisya Rizqiana; Siti Mariam; Ahmad Suriansyah; Ratna Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood character education requires the active involvement of various parties, particularly schools, families, and communities. However, in practice, there are still limitations in synergy and optimal empowerment strategies in shaping children's character holistically. This study aims to describe community empowerment strategies in shaping children's character through education at the Sabilal Muhtadin Islamic Integrated Early Childhood Education Center in Banjarmasin, which includes the leadership role of the principal, teacher empowerment, and parental involvement. This study uses a qualitative approach with a case study type. Data collection was conducted through in-depth interviews, observations, and documentation, with the principal, teachers, and parents as the main informants. Data validity was ensured through source and method triangulation, while data analysis was conducted using Miles and Huberman's interactive model, which includes data condensation, data presentation, and conclusion drawing. The results of the study show that community empowerment in character building for children takes place synergistically and sustainably. The principal implements participatory and collaborative leadership that encourages teacher involvement in the planning and implementation of character education. Teachers serve as role models through the habit of positive behavior and play activities with Islamic values, while parents are empowered through parenting programs, intensive communication, and religious activities. Collaboration between the three parties.